2022
DOI: 10.1108/aeat-08-2021-0246
|View full text |Cite
|
Sign up to set email alerts
|

Fuel flow rate modeling for descent using cuckoo search algorithm: a case study for point merge system procedure at Istanbul airport

Abstract: Purpose The purpose of this paper is to create a new fuel flow rate model using cuckoo search algorithm (CSA) for the descending stage of the flight. Design/methodology/approach Using the actual flight data record data of the B737-800 aircraft, a new fuel flow rate model has been developed for this aircraft type. The created model is to predict the fuel flow rate with high accuracy depending on the altitude and true airspeed. In addition, the CSA fuel flow rate model was used to calculate the fuel consumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…For this reason, as in other fields, the methods specified in aviation are often preferred. [20][21][22][23][24][25][26][27][28][29][30] In this study, the modeling of dimensionless decay curves, which were developed using three experimental LIDAR datasets in the RECAT-EU project and is a useful tool to characterize the wake vortex circulation decay under RWC conditions, was carried out using cuckoo search algorithm (CSA). The decay curves used in the modeling are the median (P50), 10th (P10), and 90th (P90) percentile decay curves of the RWC tracks, which constitute the top 2% longest lasting wakes.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, as in other fields, the methods specified in aviation are often preferred. [20][21][22][23][24][25][26][27][28][29][30] In this study, the modeling of dimensionless decay curves, which were developed using three experimental LIDAR datasets in the RECAT-EU project and is a useful tool to characterize the wake vortex circulation decay under RWC conditions, was carried out using cuckoo search algorithm (CSA). The decay curves used in the modeling are the median (P50), 10th (P10), and 90th (P90) percentile decay curves of the RWC tracks, which constitute the top 2% longest lasting wakes.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there are very few studies on FF rate modeling in the literature. Oruc et al (2022) have used cuckoo search algorithm found in the literature to model the FF during the landing phase of a flight. In the model they use, they estimate the FF rate based only on altitude and actual airspeed.…”
Section: Introductionmentioning
confidence: 99%